Late neurological consequences of SARS-CoV-2 infection: New challenges for the neurologist - Korchut, Agnieszka; Rejdak, Konrad (Frontiers in Neuroscience, 2023)
.Objective: To study the frequency of neurological symptoms and diseases in COVID-19 adult patients that may be late consequences of SARS-CoV-2 infection in a systematic review of the literature. Methods: Relevant studies were identified through electronic explorations of Scopus, PubMed, Google Scholar. We followed PRISMA guidelines. Data were collected from studies where the diagnosis of COVID-19 was confirmed and its late neurological consequences occurred at least 4 weeks after initial SARS-CoV-2 infection. Review articles were excluded from the study. Neurological manifestations were stratified on the basis of the frequency (above 5%, 10%, 20%) where number of studies and sample size were significant. Results: A total of 497 articles were identified for eligible content. This paper provides relevant information from 45 studies involving 9 746 patients. Fatigue, cognitive problems, smell and taste dysfunctions were the most frequent reported long-term neurological symptoms in COVID-19 patients. Other common neurological issues were paresthesia, headache and dizziness. Conclusion: On a global scale of COVID-19 affected patients, prolonged neurological problems have become increasingly recognized and concerning. Our review might be an additional source of knowledge about potential long-term neurological impacts.